Teacher's Strategy in Improving the Ability to Read and Write the Qur'an of TPA Santri during the Covid-19 Pandemic - Jumarni Jumarni (State Islamic Institute of Palopo, 2022)
This paper discusses the teacher's strategy in improving the student's ability to read and write the Qur'an of TPA Nurul Wustha Palopo during the Pandemic. The objectives of the study: (1) to find out the ability to read and write the Qur'an of Nurul Wustha TPA students during the Pandemic; (2) To find out the obstacles faced by teachers in improving the ability to read and write the Qur'an of Nurul Wustha TPA students during in the Pandemic; and (3) Describe the teacher's strategy in improving the ability to read and write the Koran of Nurul Wustha TPA students during the Pandemic. This research is qualitative research, with research subjects being the head of the TPA, teachers, students, and parents of students. Data collection techniques used are observation, interviews, and documentation. The results showed that the ability of students to read and write the Qur'an at the beginning of the Pandemic decreased due to the cessation of learning activities at the TPA, so teachers and parents sought solutions by implementing learning strategies to improve students' reading and writing skills. However, this is not free from obstacles such as internal factors such as discipline, craftsmanship, and responsibility. The second namely external factors, namely the family environment. The third is from the learning approach factor. The strategy applied by the teacher in improving the student's ability to read the Qur'an is to apply a limited face-to-face learning system at each teacher's home by applying an exposition strategy, classical individual learning, and classical reading through the Iqro method and reading with tartar. In addition, to improve the ability to write the Qur'an implemented, an online learning system through group WhatsApp training drill methods and methods of following the line as well as coloring calligraphy.